PROGNOSTIC VALUE OF P-SELECTIN IN PATIENTS WITH STABLE ANGINA PECTORIS - Khvysiuk, M. O.; Bilchenko, O. V.; Pavlov, S. B. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2018)
Coronary artery disease for many years is being the main cause of death in many developed countries. Currently, cardiovascular disease (CVD) plays the main role in the evolution of the total mortality in the world. Most deaths occur as a result of coronary heart disease (more than 300 thousand per year). It is known that chronic inflammation is a marker of global endothelial dysfunction and may be associated with the increased risk of cardiovascular events in patients with coronary artery disease. Nowadays, it is very promising in terms of assessing the prognosis and course of the disease to study P-selectin. The level of P-selectin in patients with stable angina is not associated with the level of hs-CRP, which creates the prerequisites for the personalization of therapeutic goals for reducing the systemic inflammatory response.2. In patients with high P-selectin (upper tertile), significantly more cardiovascular events are observed compared to patients with low P-selectin (lower tertile), which makes it possible to use the P-selectin level to estimate the prognosis in patients with stable angina.3. The data obtained in the study allow in the long term to use a new biomarker of inflammation of P-selectin to estimate the prognosis in patients with stable angina and to personalize therapy of patients with coronary heart disease aimed at reducing the «residual»cardiovascular risk associated with the activation of various mechanisms of the systemic inflammatory response.